Dedifferentiated Liposarcoma: A Rare Entity - Bano, Shahnaz; Singh, Bhanu Pratap; Gupta, Ankita (Annals of Pathology and Laboratory Medicine, 2024)
Background: Dedifferentiated liposarcoma is defined as well-differentiated liposarcoma juxtaposed to areas of high-grade non-lipogenic sarcoma, usually resembling fibrosarcoma or undifferentiated pleomorphic sarcoma. The retroperitoneum is a common site; fewer than 20% of dedifferentiated liposarcomas occur in the head, neck, and rarely in the subcutis. Case History: A 36-year-old male patient presented to the surgery department of our hospital with the chief complaint of a recurrence of a soft tissue mass over the left upper shoulder region. There is a history of a previous operation at the same site. In the MRI report, a well-defined lobulated lesion was noted in the subcutaneous plane over the left scapular region. The lesion is heterogeneously hyperintense on T2 and STIR and shows areas of cystic changes. A single globular skin-covered specimen measuring 10 x 6.0 x 5.0 cm. The outer surface of the skin is smooth, shiny, and varies in color from grey-white to grey-brown, with the lesion protruding from the skin (FIG 1). On the cut surface, a grayish, shiny, smooth, and cystic appearance is present. Multiple sections studied from the lesional tissue show both well-differentiated liposarcomatous and non-lipogenic (dedifferentiated) components. The liposarcomatous area consists of mature adipocytes and atypical spindle cells. Non-lipogenic components consist of highly cellular areas showing hemangiopericytoma-like vascular patterns, and in some places, malignant fibrous histiocytoma (MFH)-like areas are also noted. Discussion: Dedifferentiated liposarcoma comprises less than 10% of all liposarcomas. It is found most often in the retroperitoneum and rarely in the extremities, head, and neck region. The incidence is approximately 1 in 330,000 persons per year.